Satellite Monitoring of Water Resources in the Middle East - Shaban, Amin. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents both updated and new measurements on water resources from selective pilot areas form the Middle East. Demand for water has become very crucial notably in arid and semiarid regions like in the Middle East. The changing climate and the increased population are the most striking challenges on water resources in this region where the largest part of its territory is dry lands and deserts with minimal precipitation and high evaporation rates, and thus, the average per capita of water does not exceed 25 m3/year. This resulted in developing many studies and researches in different Middle East countries to clearly identify and assess the hydrological characteristics of the available water resources and to explore new resources in order to secure balanced water supply/demand. As a first of its type, this book introduces comprehensive knowledge on the successful reports of the use of satellite images in water studies in the Middle East, and the economic value resulted from adopting these techniques. Based on illustrated case-studies the book will represent a significant resource for a large number of experts, academics, researchers, engineers and different-level stakeholders including the decision makers. .
1. Fundamentals of Satellite Remote Sensing -- 2. Water Resources in the Middle East -- 3. The Suitability of Satellite Remote Sensing and GIS Technologies For Mapping, Monitoring and Managing Water Resources in The Middle East -- 4. Atmospheric Rivers and Precipitation in the Middle East and North Africa (MENA) -- 5. Inventory of Shared Water Resources in Western Asia Revisited: Selected Pilot Areas for the Application of Remote Sensing -- 6. GIS-based multi-criteria approach to assess water resources vulnerability in a changing climate over the Arab Domain -- 7. Unraveling the spatio-temporal dynamics of satellite-inferred water resources in the Arabian Peninsula -- 8. A Technical Note on Least Squares Mascon Fitting to GRACE Satellite Data to Estimate Total Water Storage Changes in The Middle East -- 9. Spatial-Temporal Change of a Dam Lake Area Using Remote Sensing and Meteorological Drought Indices -- 10. Forecasting Domestic Water Demand using Meteorological and Satellite data: Case study of Greater Beirut Area -- 11. MODIS Satellite Images and TRMM Products to Compare Rainfall and Streamflow along the Coastal Rivers of Lebanon -- 12. Water balance and demand for different environmental changes and management scenarios in the Hasbani Basin, Lebanon using WEAP model and remotely sensed data -- 13. Agricultural Water Management in the Nile Delta Using Remote Sensing Techniques -- 14. Studying Hydrological Characteristics of the West Bank and Gaza Strip, Palestine Using GIS and Remote Sensing Data -- 15. Landsat Satellite Images for Lineaments Detection: A Tool to Identify Groundwater Productivity in Lebanon -- 16. Using information from remote sensing to estimate groundwater: GRACE and Sentinel-1 satellites -- 17. Volcanic Terrains Reveal Bright Hydrogeological Prospects in Saudi Arabia: A GIS & RSA Linked Research on Harrat Rahat -- 18. Regional mapping of groundwater potential zones in the Saudi Arabia using remote sensing and machine learning algorithms -- 19. A DRASTIC-based Fuzzy C-Means Clustering Technique for Evaluating Groundwater Vulnerability under Uncertainty -- 20. Prospects of Retrieving Non-Optical Water Quality Properties with Remote Sensing Techniques -- 21. The potential of different reflectance based algorithms to retrieve Phycocyanin concentration through remote sensing. Application to a hypereutrophic Mediterranean lake -- 22. Remote sensing of water quality for human use of Shat Al-Hilla, Iraq.
Keywords: Water; Hydrology; Climatology; Geographic information systems; Environmental monitoring; Environmental economics; Water; Climate Sciences; Geographical Information System; Environmental Monitoring; Environmental Economics